Studying the Gas Sensitivity and Magnetic Properties of Magnesium Ferrite Prepared by the Sol-Gel Route - Mahdi , Hussein I.; Bakr, Nabeel A.; Al-Saadi, Tagreed M. (Iraqi Journal of Science, 2024)
Nickel-doped manganese–magnesium ferrite (NixMn0.25-xMg0.75Fe2O4) was prepared using the auto-combustion method. X-ray diffraction patterns showed a single ferrite spinel phase in all the prepared samples. The crystallite size ranged from 24.30 to 28.32 nm, increasing with increasing the Ni content. The porous structure of all the samples was verified with a scanning electron microscope. FE-SEM images were used to confirm the production of spherical or semi-spherical nanoparticles with little change in particle size distribution. The study revealed that the nanoparticles were small enough to behave superparamagnetically. According to the magnetic tests conducted with the VSM at room temperature, the hysteresis loop region is practically non-existent, indicating typical soft magnetic materials. In addition, the conductance responses of the magnesium ferrite nanocomposite were measured by exposing it to the oxidizing gas (NO2) at different operating temperatures. The results showed that the sensor with the nano ferrite sample of (x = 0.20) has a good sensitivity of 707.22% as well as response and recovery times.